Inertial measurement units are 'all g': Inter-trial reliability when assessing upper and lower body impact loading in artistic gymnastics. Issue 2 (April 2021) - Campbell, Rhiannon A; Bradshaw, Elizabeth J; Ball, Nick; Hunter, Adam; Spratford, Wayne
The magnitude of loading artistic gymnasts experience during training is currently unknown. Inertial measurement units (IMUs) could assess loading, although the reliability of these devices must be established prior to implementation into the training environment. This study aimed to determine inter-trial reliability of using IMeasureU Blue Thunder IMUs to assess upper and lower limb loading when performing foundation gymnastics skills. A secondary aim investigated the effect of raw and filtered acceleration signals on reliability results. Sixteen competitive level artistic gymnasts (male, n = 8; female, n = 8) performed seven gymnastics skills while wearing four IMUs (upper back, lower back, forearm and tibia). The peak resultant acceleration (PRA) during ground contact for all skills was exported from raw and filtered acceleration data (fourth-order zero-lag Butterworth filter with 85 Hz cut-off). Descriptive statistics (median and inter-quartile range), Friedman's ANOVA, intra-class correlations, coefficient of variation, mean difference and Cohen's effect sizes were calculated. Overall, the IMU PRA measures showed very good inter-trial reliability, however filtered signals improved reliability statistics for five variables compared to raw. The forearm- and tibia-mounted IMUs demonstrated improved reliability (very good reliability) compared to back positions (good reliability). IMUs are considered reliable devices to measure upper and lower limb loading in gymnastics.